Design and fabrication of innovative egg breaker and egg yolk separator machine / Muhammad Fathurrahman Muizuddin - Muizuddin, Muhammad Fathurrahman (2023)
Egg yolk and egg white are hard to separate by a person without experience and may take some time to separate them. People that work in the kitchen do not have a proper way to separate it without wasting a lot of time. The goal of this design is to make an automated egg breaker and egg yolk separator machine for kitchen people to make their job easy and make it easy to get at an affordable price. This machine also can make as home kitchen equipment because the size is not too big for home use. This machine has the potential for a home baker or small bakery that needs to take time to separate the egg yolk from the egg white. Then, Egg Breaker and Egg Yolk Separator were created to solve this issue